Climate change vis-a-vis Indian agriculture - Dagar, J.C.; Singh, A.K.; Singh, Rajbir; Arunachalum, A. Arunachalum (Annals of Agricultural Research, 2014)
Climate change and variability are posing the serious challenges influencing the performance of Indian agriculture. The fourth IPCC report clearly brought out the global and regional impacts of projected climate change on agriculture. India being a large country with diverse agro-climatic regions is more vulnerable in view of huge population dependant on agriculture and poor coping mechanism. There are evidences already of negative impacts on yield of wheat, rice and other crops in parts of India due to increased temperature, increased water stress and reduction in number of rainy days which in turn would result in greater instability in food production. Researchers and policy framers should develop a comprehensive adaptation and mitigation strategies for coping the adverse impact of climate change. Changes in land use management, development of multiple stress tolerant varieties, efficient cropping systems that match with changed rainfall patterns, resource conservation technologies, water harvesting and supplemental irrigation for drought proofing in rainfed areas can help in mitigating the adverse impact of climate change and variability. Alternate land use system like agro-forestry system and other biological carbon capture systems can also help in both adaptation and mitigation. Reliable early warning system of environmental changes and their spatial and temporal magnitude will be of quite help and policies to support the diffusion of this information and to help interpret these forecasts in terms of their agronomic and economic implications are required to help farmers in a big way.